Lyophilized Fruit Juice of Citrus sinensis Triggers Mitochondria-mediated Apoptosis via Downregulation of PI3K/AKT in MCF-7 Cell Line - Mathiyazhagan, Jayasindu; Daniel, John Arul; Doss, George Priya C.; Jayaraj, Rama; Gothandam, Kodiveri Muthukaliannan (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Breast cancer is prevalent cancer among women and a major cause of death worldwide due to various genetic and environmental factors. Citrus sinensis is widely taken fruit juice in most countries that are believed to reduce breast cancer risk. However, the mechanism through which it acts remains unclear. Our objective was to explore the mechanism through which Citrus sinensis acts as a cytotoxic agent. Materials and Methods: FT-IR and GC-MS analyses of lyophilzed orange juice (LOJ) were performed to find phytocompounds that were subjected to in silico docking analysis against phosphatidylinositol-3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway. The proteins that showed the low free energy of binding was taken for gene expression analysis. RT-PCR analysis was carried out to observe PI3K/AKT/mTOR genes inhibition in LOJ treated cells. Cytotoxicity, apoptosis, caspase 9 activity were performed against the human breast cancer cell line (MCF-7). Results: The docking analysis against PI3K/AKT/mTOR with LOJ compounds showed the best interactions. Further down-regulation of PI3K/AKT and moderate up-regulation of mTOR was confirmed using gene expression analysis. LOJ showed concentration-dependent cytotoxicity, apoptosis, decreased mitochondrial membrane stability and caspase 9 against the MCF-7 cell line. Conclusion: This study concludes that LOJ can induce apoptosis in MCF-7 cells via PI3K and AKT inhibition.
Keywords: Lyophilized orange juice; Molecular docking; Apoptosis; MCF-7 cell line; PI3K/AKT/mTOR